Water-cooled wall self-cleaning infrared energy-saving coating, preparation method and application

By using a combination of base and surface coatings on the water-cooled wall, the problems of coking, dust accumulation, corrosion and low heat transfer efficiency of the water-cooled wall are solved, self-cleaning and wear-resistant effects are achieved, and the service life and operating efficiency of the water-cooled wall are improved.

CN120665464AActive Publication Date: 2025-09-19KAIBEN (TIANJIN) NEW MATERIAL TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510900269.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-01
Publication Date
2025-09-19
Estimated Expiration
2045-07-01

AI Technical Summary

Technical Problem

Water-cooled walls in coal-fired boilers face problems such as coking and ash accumulation, corrosion, overheating of the tube walls, and high carbon content in the ash. Existing technologies are difficult to effectively solve these problems, resulting in reduced heat transfer efficiency and increased maintenance costs.

Method used

The water-cooled wall self-cleaning infrared energy-saving coating, which includes a base layer and a surface layer, is used. The base layer is composed of silicon carbide, aluminum oxide, zirconium oxide and other materials to form a heat-conducting network, and the surface layer is composed of silicon carbide, zirconium oxide and brown corundum to form a wear-resistant system. The oxidation reaction is carried out in combination with a catalyst at the base layer to inhibit dust accumulation and improve thermal efficiency.

Benefits of technology

It reduces dust accumulation, extends coating life, reduces maintenance costs, improves heat transfer efficiency and wear resistance, prevents corrosion, and increases the service life and operational stability of the water-cooled wall.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a self-cleaning infrared energy-saving coating for a water cooling wall as well as a preparation method and application thereof, and belongs to the field of inorganic refractory materials. According to the prime paint, silicon carbide serves as a heat conduction network body, cordierite and boron nitride are matched to form a multi-stage buffer network, the thermal expansion coefficient of a metal matrix is accurately matched, thermal cycle cracking is inhibited, aluminum oxide and zirconium oxide enhance corrosion resistance and anti-stripping capacity, a water glass-polyacrylamide-sodium tripolyphosphate composite bonding system guarantees adhesive force, and the corrosion resistance of the metal matrix is improved. The catalyst is loaded in the heat-conducting network, so that catalysis in an optimal temperature zone is facilitated, and self-cleaning is realized; according to the surface coating, high-proportion silicon carbide is combined with zirconium oxide and brown aluminum oxide to form a super-hard wear-resistant system, scouring is resisted, high-temperature stability is guaranteed through a second binder, the thermal efficiency is improved through heat conduction network optimization and infrared radiation performance, and meanwhile, by means of catalytic self-cleaning, wear-resistant and corrosion-resistant structural design, the service life of the coating is prolonged. The technical effects of reducing accumulated dust, prolonging the service life of the coating and reducing the maintenance cost are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of inorganic refractory materials, and in particular relates to a water-cooled wall self-cleaning infrared energy-saving coating, a preparation method and an application thereof. Background Art

[0002] As a key heat transfer component of coal-fired boilers, the water-wall system bears the core functions of absorbing furnace radiant heat, protecting the furnace wall, and maintaining steam temperature. However, during long-term high-temperature and high-pressure operation, the water-wall tubes face multiple complex problems: Coking and ash accumulation: Fuel ash melts and adheres to the pipe wall surface to form a dense coke layer (especially when the flue gas temperature is higher than the ash melting point). Since its thermal resistance coefficient can be up to 300-500 times that of the metal pipe, it will significantly reduce the heat transfer efficiency, cause the exhaust gas temperature to rise, and increase coal consumption; High-temperature corrosion: SO3, HCl, and molten ash generated by the combustion of high-sulfur and high-chlorine fuels corrode the pipe wall metal, causing pipe wall thinning and even pipe bursting. The typical corrosion rate can reach 2-5mm / year; Overheating of the pipe wall: The thermal insulation effect of the coking layer can easily cause the local pipe wall temperature to exceed the design value by 50-150°C, which will increase the risk of material creep failure; High carbon content in ash: Unburned carbon particles are captured by the coke layer, which hinders the final combustion of the carbon particles, causing the carbon content of the fly ash to increase and reduce combustion efficiency.

[0003] Studies have shown that heat transfer losses caused by coking and ash accumulation on the water-cooled walls account for 12-18% of the total heat loss of the boiler, and the ash layer reduces the infrared emissivity of the tube wall from 0.85 to 0.35, significantly weakening the efficiency of radiation heat transfer.

[0004] There are three main ways in existing technology to improve the coking and dust accumulation on water-cooled walls: 1. Physical Intervention Mechanical dust removal mainly uses steam blowing, infrasonic dust removal and steel ball de-dusting. Its removal rate is low and it is ineffective for sticky dust accumulation. It also consumes a lot of energy and accelerates pipe wall wear. Thermodynamic control can prevent coking and ash accumulation by lowering the furnace temperature to below the ash melting point, but it will reduce combustion efficiency and significantly increase NOx generation.

[0005] 2. Fuel Pretreatment Additive modification: adding kaolin can increase the ash melting point, but it will increase the amount of ash residue and aggravate pipe wall wear; adding limestone can absorb SO3 and thus reduce the generation of sticky sulfate, but it will cause low-temperature scaling; adding magnesium oxide can react with silicate to form high-melting-point forsterite, but it will lead to a significant increase in cost; Strictly controlling the coal powder fineness R90 < 6% can promote ash burnout, but its processing cost accounts for 18-25% of the total fuel cost.

[0006] 3. Water wall coating modification Existing technologies primarily utilize metallization, thermal sprayed ceramics, and enamel coatings. Metallization increases surface hardness and prevents dust accumulation through a Cr-Al diffusion layer, but when temperatures reach 1100°C, Cr2O3 evaporates, causing it to lose its function. Thermal sprayed ceramics prevent dust accumulation by forming a dense Al2O3-TiO2 barrier, but this can easily lead to cracking due to the large difference in thermal expansion coefficients between the materials. Enamel coatings isolate dust through a glassy layer, but are extremely susceptible to flaking.

[0007] Low surface energy coatings (such as modified polytetrafluoroethylene) can also be used in existing technologies to reduce ash adhesion. However, it is not heat-resistant and fails in the high-temperature area of ​​the furnace. There are also photocatalytic coating technology and conductive coating technology, but they are difficult to implement because it is difficult to deploy ultraviolet light and high-voltage electrodes in the furnace. Summary of the Invention

[0008] In order to solve the above technical problems of the prior art, the present invention aims to provide a water-cooled wall self-cleaning infrared energy-saving coating, a preparation method and an application thereof.

[0009] One of the purposes of the present invention is to provide a water-cooled wall self-cleaning infrared energy-saving coating, the coating comprising a base coating and a surface coating; The primer comprises the following raw materials in parts by weight: Thermally conductive aggregate, comprising 18-22 parts of silicon carbide, 4-6 parts of cordierite, 4-6 parts of boron nitride, 5-7 parts of aluminum oxide, and 5-7 parts of zirconium oxide; 4-6 parts of catalyst, including copper oxide and / or iron oxide; The first binder comprises 20-30 parts of water glass, 0.1-1 parts of polyacrylamide and 0.1-1 parts of sodium tripolyphosphate; 0.1-0.5 parts of the first surfactant; First defoamer, 0.1~0.3 parts; The first auxiliary agent includes 0.5-2 parts of bentonite, 0.05-0.2 parts of hydroxymethyl cellulose and 2-4 parts of Texanol ester alcohol; 5-30 parts water; The surface coating comprises the following raw materials in parts by weight: Wear-resistant aggregate, including 25-35 parts of silicon carbide, 5-7 parts of zirconium oxide and 4-6 parts of brown corundum; The second adhesive includes 25 to 35 parts of sj-8050 high temperature adhesive; 0.1-0.5 parts of the second surfactant; Second defoaming agent, 0.1~0.3 parts; The second auxiliary agent includes 0.5-2 parts of bentonite, 0.05-0.2 parts of hydroxymethyl cellulose and 2-4 parts of Texanol ester alcohol; 5~30 parts water

[0010] Preferably, the particle size of silicon carbide in the primer is D50=7~9 μm, the particle size of the catalyst is 150~250 nm, and the particle size of silicon carbide in the topcoat is D50=5~7 μm.

[0011] Preferably, the mass ratio of the catalyst to silicon carbide in the primer is 1:3.5-4.5.

[0012] Preferably, the mass ratio of cordierite to boron nitride in the primer is 1:(0.9-1.1).

[0013] A second object of the present invention is to provide a method for preparing the infrared energy-saving coating as described above, wherein the method for preparing the primer coating comprises: First, water glass precursor is prepared using water glass, sodium tripolyphosphate and polyacrylamide; bentonite solution with a concentration of 5% is prepared using bentonite and water; and hydroxymethyl cellulose solution with a concentration of 2% is prepared using hydroxymethyl cellulose and water; Then, add water glass precursor, bentonite solution, hydroxymethyl cellulose solution, surfactant and defoamer in sequence, stir at 300-600 rpm for 30 minutes, then add thermal conductive aggregate, stir at low speed of 40-60 rpm for 30 minutes, then stir at high speed of 1000 rpm for 2 hours, then add remaining water, stir at 300-600 rpm for 45 minutes; The preparation method of the surface coating comprises: First, prepare bentonite solution and hydroxymethyl cellulose solution in the same way as the primer; Then, add component A of sj-8050 high-temperature binder and add component B while stirring at 300-500 rpm, continue stirring for 3 hours, then add bentonite liquid, hydroxymethyl cellulose liquid, surfactant, and defoaming agent in turn, stir evenly, add wear-resistant aggregate, first stir at a low speed of 40-60 rpm for 30 minutes, then stir at a high speed of 1000 rpm for 1 hour, add the remaining water, and stir at 300-600 rpm for 45 minutes.

[0014] The third object of the present invention is to provide an application of the infrared energy-saving coating as described above in a water-cooled wall coating, wherein the water-cooled wall coating includes a bottom layer and a surface layer, wherein the bottom layer is located between the water-cooled wall and the surface layer, the bottom layer has a thickness of 50~150μm, and the surface layer has a thickness of 40~100μm.

[0015] Preferably, the method for treating the water-cooled wall coating includes: First, the roughness of the water-cooled wall was treated by sandblasting to Rz = 40~80μm, and the viscosity of the base coating and the surface coating was adjusted to 1.35~1.45Pa·s; Then, spray the primer on the water-cooled wall and dry it at 20-30℃ for 24h. The thickness of the primer after drying is 20-150μm. Then, the topcoat is sprayed on the base layer and dried at 20-30°C for 24 hours. The thickness of the base layer after drying is 40-100 μm.

[0016] Preferably, the coating treatment method further comprises the step of performing a curing treatment after the surface coating is dried; The curing process includes: first heating to 80°C at a rate of 2°C / min, keeping warm for 60 minutes, then heating to 150°C at a rate of 1.5°C / min, keeping warm for 30 minutes, then heating to 250°C at a rate of 3°C / min, keeping warm for 45 minutes, then cooling to 80°C at a rate of 1°C / min, and then cooling naturally.

[0017] Preferably, the bottom layer thermal expansion coefficient CTE = (9.2~9.8) × 10 -6 / K.

[0018] Preferably, the wetting angle of the surface layer is greater than 90°.

[0019] The beneficial effects of the present invention include: The self-cleaning infrared energy-saving coating for water-cooled walls described in the present invention achieves multiple functions through the coordinated design of the base layer and the surface layer: the base layer coating uses silicon carbide as the main body of the thermal conductive network, and is combined with cordierite and boron nitride to form a multi-level buffer network, accurately matching the thermal expansion coefficient of the metal substrate to inhibit thermal cycle cracking, while alumina and zirconia enhance corrosion resistance and anti-stripping capabilities, and the water glass-polyacrylamide-sodium tripolyphosphate composite bonding system ensures adhesion. The catalyst is loaded in the thermal conductive network, which is conducive to catalysis in the optimal temperature zone and self-cleaning. The surface coating uses a high proportion of silicon carbide combined with zirconium oxide and brown corundum to form an ultra-hard and wear-resistant system to resist erosion, and the sj-8050 high-temperature adhesive ensures high-temperature stability. The overall thermal efficiency is improved through the optimization of the thermal conductive network and the infrared radiation performance. At the same time, the catalytic self-cleaning and wear-resistant and corrosion-resistant structural design achieve the technical effects of reducing dust accumulation, extending the coating life, and reducing maintenance costs. Furthermore, there is good wettability between the surface coating and the base coating, and the surface coating can penetrate into the micropores of the base coating, which is beneficial to secondary sealing of the micropores of the base coating, thereby isolating the contact between the furnace gas and the water-cooled wall, and helping to avoid chemical corrosion of the water-cooled wall by chemical gases in the furnace gas. DETAILED DESCRIPTION

[0020] In the following description, certain specific details are included to provide a thorough understanding of each disclosed embodiment. However, one skilled in the relevant art will recognize that the embodiments can be implemented without one or more of these specific details and with other methods, components, materials, etc.

[0021] Unless otherwise required herein, throughout the specification and claims that follow, the words "include" and "comprising" should be interpreted in an open, inclusive sense, ie, "including but not limited to."

[0022] Reference throughout this specification to "one embodiment" or "an embodiment" or "a preferred embodiment" or "certain embodiments" means that at least one embodiment includes the specific referenced elements, structures, or features described in connection with that embodiment. Thus, appearances of the phrases "in one embodiment" or "in an embodiment" or "in a preferred embodiment" or "in certain embodiments" in various places throughout this specification are not necessarily all referring to the same embodiment. Furthermore, the specific elements, structures, or features may be combined in any suitable manner in one or more embodiments.

[0023] According to a first aspect of the present invention, there is provided a water-cooled wall self-cleaning infrared energy-saving coating, the coating comprising a primer and a surface coating; The primer comprises the following raw materials in parts by weight: Thermally conductive aggregate, comprising 18-22 parts of silicon carbide, 4-6 parts of cordierite, 4-6 parts of boron nitride, 5-7 parts of aluminum oxide, and 5-7 parts of zirconium oxide; 4-6 parts of catalyst, including copper oxide and / or iron oxide; The first binder comprises 20-30 parts of water glass, 0.1-1 parts of polyacrylamide and 0.1-1 parts of sodium tripolyphosphate; 0.1-0.5 parts of the first surfactant; First defoamer, 0.1~0.3 parts; The first auxiliary agent includes 0.5-2 parts of bentonite, 0.05-0.2 parts of hydroxymethyl cellulose and 2-4 parts of Texanol ester alcohol; 5-30 parts water; In the present invention, the primer is used to form the bottom layer of the water-cooled wall coating.

[0024] Among the components of the primer, the thermal conductive aggregate includes 18 to 22 parts of silicon carbide, 4 to 6 parts of cordierite, 4 to 6 parts of boron nitride, 5 to 7 parts of aluminum oxide and 5 to 7 parts of zirconium oxide.

[0025] Silicon carbide is used to form the main body of the heat-conducting network. The amount of silicon carbide used is, for example, 18 parts, 18.5 parts, 19 parts, 19.5 parts, 20 parts, 20.5 parts, 21 parts, 21.5 parts or 22 parts.

[0026] Cordierite has a low coefficient of thermal expansion and good thermal shock resistance, matching the expansion and contraction of the metal substrate and reducing the risk of stress cracking in the coating due to thermal cycling. Cordierite can be used in amounts of, for example, 4 parts, 4.2 parts, 4.4 parts, 4.6 parts, 4.8 parts, 5 parts, 5.2 parts, 5.4 parts, 5.6 parts, 5.8 parts, or 6 parts.

[0027] Cordierite has anisotropic thermal expansion in the a, b, and c axis directions. In the composite material, the grains in different directions are randomly distributed, which can form an internal micro-strain offset effect.

[0028] Boron nitride has high in-plane thermal conductivity, can eliminate hot spots by rapid heat conduction, reduce local thermal stress, and the lamellar structure of boron nitride can also absorb strain energy by slippage, dissipate stress, prevent crack propagation, and improve coating toughness. At the same time, boron nitride is a low modulus material that can absorb impact energy when stressed, reducing the risk of brittle fracture. The consumption of boron nitride is, for example, 4 parts, 4.2 parts, 4.4 parts, 4.6 parts, 4.8 parts, 5 parts, 5.2 parts, 5.4 parts, 5.6 parts, 5.8 parts or 6 parts.

[0029] Cordierite and boron nitride work together to precisely control the thermal expansion coefficient of the coating's underlying layer, creating a gradient match between the coating and the steel substrate, thereby inhibiting thermal cycling cracking.

[0030] Cordierite disperses stress through lattice anisotropy and microcracks, while boron nitride dissipates stress through interlayer slip, forming a multi-level buffer network. Boron nitride's lamellar structure deflects crack paths, while cordierite's microcracks prevent the main crack from extending. Together, they resist crack propagation. Together with other components, they help the coating better match the metal substrate and maintain structural stability.

[0031] Alumina has high hardness, a high melting point, wear resistance, and chemical inertness. It provides structural strength, high temperature resistance, corrosion resistance, and protection for the underlying layer. Alumina can be used in amounts of, for example, 5 parts, 5.2 parts, 5.4 parts, 5.6 parts, 5.8 parts, 6 parts, 6.2 parts, 6.4 parts, 6.6 parts, 6.8 parts, or 7 parts.

[0032] Zirconia has high toughness and a high melting point, primarily used to improve the coating's impact and spalling resistance, compensating for the brittleness of high-hardness materials. Its low thermal conductivity also creates a thermal resistance gradient within the underlying layer, helping to diffuse heat more evenly toward the surface and preventing localized overheating. Zirconia can be used in amounts of, for example, 5 parts, 5.2 parts, 5.4 parts, 5.6 parts, 5.8 parts, 6 parts, 6.2 parts, 6.4 parts, 6.6 parts, 6.8 parts, or 7 parts.

[0033] In the primer, silicon carbide forms the backbone of an efficient heat transfer network, while cordierite and boron nitride synergistically form a multi-level buffer network. These two components, along with other components, help the coating better match the metal substrate and maintain structural stability. Alumina and zirconium oxide synergistically enhance the coating's corrosion resistance.

[0034] In the present invention, the first binder includes 20-30 parts of water glass, 0.1-1 part of polyacrylamide and 0.1-1 part of sodium tripolyphosphate.

[0035] Water glass has a modulus of 2.5 to 3.5 and can dehydrate and solidify at high temperatures to form a silica network, providing high-strength inorganic bonding, high-temperature resistance, and non-flammability. This is key to the bond between the coating and the metal substrate and aggregate.

[0036] Polyacrylamide is used to improve the rheological properties of coatings during construction. It has thickening and anti-sagging functions, can enhance the wet adhesion of the coating, and improve the flexibility and crack resistance of the coating during the initial drying and curing stages.

[0037] Sodium tripolyphosphate helps to disperse aggregate particles, prevent agglomeration and sedimentation, and improve the uniformity and stability of the coating.

[0038] Waterglass, polyacrylamide, and sodium tripolyphosphate form an organic-inorganic composite bonding system. Waterglass provides ultimate high-temperature strength and inorganic bonding, polyacrylamide improves workability and initial performance, and sodium tripolyphosphate ensures system stability. Together, these three components guarantee coating integrity and adhesion during application, curing, and operation.

[0039] The catalyst is used in an amount of, for example, 4 parts, 4.2 parts, 4.4 parts, 4.6 parts, 4.8 parts, 5 parts, 5.2 parts, 5.4 parts, 5.6 parts, 5.8 parts, or 6 parts, and includes copper oxide and / or iron oxide. Under the high temperature environment of boiler operation, the copper oxide and iron oxide can catalyze the oxidation reaction of carbon deposits generated by incomplete combustion of fuel and organic pollutants adhered to the coating surface. The catalyst is, for example, copper oxide, iron oxide, or a combination of copper oxide and iron oxide, preferably copper oxide.

[0040] In the present invention, the catalyst is arranged at the bottom layer of the water-cooled wall coating. Since the temperature of the bottom layer is lower than that of the surface layer, on the one hand, it can ensure that the catalytic reaction of the catalyst is in the optimal temperature range, such as the optimal temperature range of CuO is 500-800°C; on the other hand, it can avoid high-temperature sintering of the surface layer, because when the temperature exceeds 1000°C, the catalyst grains grow, which will greatly reduce the catalyst activity.

[0041] In this invention, the catalyst in the bottom layer activates oxygen, converting lattice oxygen into reactive oxygen radicals. These reactive oxygen species diffuse toward the coating surface, oxidizing the surface fly ash. Because the catalyst is supported within a thermally conductive silicon carbide network, high-temperature heat is rapidly transferred to the catalytic sites. Furthermore, the silicon carbide acts as a "conductive bridge," accelerating electron transfer and promoting the formation of reactive oxygen radicals, thereby promoting efficient catalytic reactions.

[0042] The first surfactant can reduce the surface tension of the coating, improve its wettability on the metal substrate and aggregate particles, make the coating easier to spread and penetrate into the micropores of the substrate, improve adhesion, and also contribute to dispersion stability. The first surfactant is used in an amount of, for example, 0.1 part, 0.2 part, 0.3 part, 0.4 part, or 0.5 part.

[0043] Specifically, the first surfactant is a nonionic surfactant, including a JFC surfactant.

[0044] The first defoamer is used to eliminate or suppress the generation of bubbles during the coating preparation and application process, thereby preventing the formation of pinholes, defects, etc. that may reduce the density, strength, adhesion, and protective properties of the coating. The first defoamer is used in an amount of, for example, 0.1 part, 0.15 part, 0.2 part, 0.25 part, or 0.3 part.

[0045] Specifically, the first defoaming agent includes an organic silicon surfactant.

[0046] The first auxiliary agent includes 0.5-2 parts of bentonite, 0.05-0.2 parts of hydroxymethyl cellulose and 2-4 parts of Texanol ester alcohol.

[0047] Bentonite imparts thixotropy to the coating, preventing aggregate from settling during storage and application, and improving application performance. The bentonite is used in amounts of, for example, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, or 2 parts.

[0048] Hydroxymethyl cellulose is used to increase viscosity, improve leveling, slow water evaporation, extend open time, and reduce drying cracks. The amount of hydroxymethyl cellulose used is, for example, 0.05 part, 0.06 part, 0.07 part, 0.08 part, 0.09 part, 0.1 part, 0.11 part, 0.12 part, 0.13 part, 0.14 part, 0.15 part, 0.16 part, 0.17 part, 0.18 part, 0.19 part, or 0.2 part.

[0049] Texanol ester alcohol is used to promote better film formation of the coating and improve the continuity and density of the paint film. The amount of Texanol ester alcohol used is, for example, 2 parts, 2.2 parts, 2.4 parts, 2.6 parts, 2.8 parts, 3 parts, 3.2 parts, 3.4 parts, 3.6 parts, 3.8 parts or 4 parts.

[0050] The three work together to optimize the coating's rheological properties, storage stability, construction performance and film-forming quality.

[0051] The surface coating comprises the following raw materials in parts by weight: Wear-resistant aggregate, including 25-35 parts of silicon carbide, 5-7 parts of zirconium oxide and 4-6 parts of brown corundum; The second adhesive includes 25 to 35 parts of sj-8050 high temperature adhesive; 0.1-0.5 parts of the second surfactant; Second defoaming agent, 0.1~0.3 parts; The second auxiliary agent includes 0.5-2 parts of bentonite, 0.05-0.2 parts of hydroxymethyl cellulose and 2-4 parts of Texanol ester alcohol; 5~30 parts water

[0052] In the present invention, the surface coating material is used to form the surface layer of the water-cooled wall coating.

[0053] Among the components of the surface coating, the wear-resistant aggregate includes 25-35 parts of silicon carbide, 5-7 parts of zirconium oxide and 4-6 parts of brown corundum.

[0054] Silicon carbide is used to form the main body of the thermal conductive network, and the amount of silicon carbide used is, for example, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, or 35 parts. In the surface coating, silicon carbide accounts for a large proportion, which helps to improve the basic wear resistance of the surface.

[0055] Zirconia is used in the surface layer to improve its resistance to mechanical impact and thermal shock, preventing cracking and spalling. Its low thermal conductivity also helps maintain surface temperature, facilitating infrared radiation. Zirconia can be used in amounts of, for example, 5 parts, 5.2 parts, 5.4 parts, 5.6 parts, 5.8 parts, 6 parts, 6.2 parts, 6.4 parts, 6.6 parts, 6.8 parts, or 7 parts.

[0056] Brown corundum, the core wear-resistant component, can withstand the erosion and abrasion of high-speed ash and coal dust in the furnace, protecting the bottom layer and substrate. It also has high temperature resistance and chemical stability. The dosage of brown corundum is, for example, 4 parts, 4.2 parts, 4.4 parts, 4.6 parts, 4.8 parts, 5 parts, 5.2 parts, 5.4 parts, 5.6 parts, 5.8 parts, or 6 parts.

[0057] In this invention, brown corundum, zirconium oxide, and silicon carbide work together to form an ultra-hard composite wear-resistant system. The brown corundum resists wear, the zirconium oxide absorbs impact energy to prevent brittle failure, and the silicon carbide maintains the heat conduction path. This overall system ensures the surface layer remains effective in harsh erosion environments.

[0058] The second adhesive uses sj-8050 high temperature adhesive, and the amount of the second adhesive is, for example, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts or 35 parts.

[0059] Specifically, the second adhesive is Sanjin Company's SJ-8050 high-temperature adhesive, which includes component A and component B. It has high-strength bonding properties and is particularly suitable for the wear-resistant aggregate system described in the present invention, as well as excellent high-temperature stability, and can remain stable for a long time at high boiler temperatures.

[0060] The second surfactant can reduce the surface tension of the coating, improve its wettability on the metal substrate and aggregate particles, make the coating easier to spread and penetrate into the micropores of the substrate, improve adhesion, and also contribute to dispersion stability. The second surfactant is used in an amount of, for example, 0.1 part, 0.2 part, 0.3 part, 0.4 part, or 0.5 part.

[0061] Specifically, the second surfactant is a nonionic surfactant, including a JFC surfactant.

[0062] The second defoamer is used to eliminate or suppress the generation of bubbles during the coating preparation and application process, thereby preventing the formation of pinholes, defects, etc. that may reduce the density, strength, adhesion, and protective properties of the coating. The dosage of the second defoamer is, for example, 0.1 part, 0.15 part, 0.2 part, 0.25 part, or 0.3 part.

[0063] Specifically, the second defoaming agent includes an organic silicon defoaming agent.

[0064] The second auxiliary agent includes 0.5-2 parts of bentonite, 0.05-0.2 parts of hydroxymethyl cellulose and 2-4 parts of Texanol ester alcohol.

[0065] Bentonite imparts thixotropy to the coating, preventing settling during storage and application, and improving application performance. The bentonite is used in an amount of, for example, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 part, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, 1.6 parts, 1.7 parts, 1.8 parts, 1.9 parts, or 2 parts.

[0066] Hydroxymethyl cellulose is used to increase viscosity, improve leveling, slow water evaporation, extend open time, and reduce drying cracks. The amount of hydroxymethyl cellulose used is, for example, 0.05 part, 0.06 part, 0.07 part, 0.08 part, 0.09 part, 0.1 part, 0.11 part, 0.12 part, 0.13 part, 0.14 part, 0.15 part, 0.16 part, 0.17 part, 0.18 part, 0.19 part, or 0.2 part.

[0067] Texanol ester alcohol is used to promote better film formation of the coating and improve the continuity and density of the paint film. The amount of Texanol ester alcohol used is, for example, 2 parts, 2.2 parts, 2.4 parts, 2.6 parts, 2.8 parts, 3 parts, 3.2 parts, 3.4 parts, 3.6 parts, 3.8 parts or 4 parts.

[0068] The three work together to optimize the coating's rheological properties, storage stability, construction performance and film-forming quality.

[0069] In a preferred embodiment of the present invention, the particle size D50 of silicon carbide in the primer is 7-9 μm, and the particle size of the catalyst is 150-250 nm.

[0070] In the present invention, silicon carbide with a particle size of 7 to 9 μm can increase the packing density and form a continuous interpenetrating heat-conducting network at the bottom layer, thereby reducing the interface thermal resistance and optimizing the heat-conducting network.

[0071] The catalyst particle size is controlled at 150~250nm, which can provide sufficient active sites, avoid the migration and agglomeration of nanoparticles at high temperatures and ensure low-temperature reaction activity. The synergistic effect of silicon carbide and catalyst particle size can form a "pebble-sand" filling model, in which silicon carbide forms the skeleton and the catalyst fills the gaps, which is beneficial to improving catalytic efficiency.

[0072] In a preferred embodiment of the present invention, the particle size D50 of silicon carbide in the surface coating is 5-7 μm.

[0073] In the present invention, on the one hand, 5~7μm silicon carbide and brown corundum form a dual-scale wear-resistant system, the brown corundum particle size is generally 10~20μm, and fine-grained silicon carbide fills the gaps in the brown corundum, which can reduce stress concentration points; on the other hand, 5~7μm silicon carbide is conducive to forming a smooth surface and reducing ash adhesion points; on the third hand, fine particles are more likely to form a continuous infrared radiation surface in the high-temperature binder, thereby improving the infrared emissivity.

[0074] In a preferred embodiment of the present invention, the mass ratio of the catalyst to silicon carbide in the primer is 1:3.5-4.5.

[0075] In the present invention, when the mass ratio of the catalyst to silicon carbide is 1:3.5~4.5, the catalyst is evenly dispersed on the surface of the silicon carbide particles to form a core-shell composite structure, which can optimize the active sites. At the same time, due to the rapid transfer of heat, the catalytic reaction rate can be greatly improved; and the reaction heat can be quickly extracted, which is more conducive to avoiding catalyst sintering. When the mass ratio of the catalyst to silicon carbide is 1:3.5~4.5, the volume of silicon carbide accounts for 65~70%, forming a continuous rigid skeleton, which is beneficial to improving the mechanical strength of the coating. When the mass ratio of the catalyst to silicon carbide is less than 1:3.5, it is easy to block the heat channel, which may lead to accelerated sintering and increased costs. When the mass ratio of the catalyst to silicon carbide is greater than 1:4.5, the catalytic active sites are insufficient, which may lead to a decrease in the self-cleaning effect.

[0076] In the present invention, the mass ratio of the catalyst to silicon carbide is, for example, 1:3.5, 1:3.6, 1:3.7, 1:3.8, 1:3.9, 1:4, 1:4.1, 1:4.2, 1:4.3, 1:4.4, or 1:4.5.

[0077] In a preferred embodiment of the present invention, the mass ratio of cordierite to boron nitride in the primer is 1:(0.9-1.1).

[0078] In the present invention, when the cordierite to boron nitride mass ratio is 1:0.9 to 1.1, the cordierite, as equiaxed particles, forms a rigid skeleton, while the boron nitride, as a lamellar structure, fills the gaps, forming an interpenetrating thermal conductive and toughening network. This is also more conducive to precisely controlling the thermal expansion coefficient of the coating to match that of the steel substrate. Examples of the cordierite to boron nitride mass ratio are 1:0.9, 1:0.92, 1:0.94, 1:0.96, 1:0.98, 1:1, 1:1.02, 1:1.04, 1:1.06, 1:1.08, or 1:1.1.

[0079] According to a second aspect of the present invention, a method for preparing the infrared energy-saving coating as described above is provided, wherein the method for preparing the primer coating comprises: First, water glass precursor is prepared using water glass, sodium tripolyphosphate and polyacrylamide; bentonite solution with a concentration of 5% is prepared using bentonite and water; and hydroxymethyl cellulose solution with a concentration of 2% is prepared using hydroxymethyl cellulose and water; Then, add water glass precursor, bentonite solution, hydroxymethyl cellulose solution, surfactant and defoamer in sequence, stir at 300-600 rpm for 30 minutes, then add thermal conductive aggregate, stir at low speed of 40-60 rpm for 30 minutes, then stir at high speed of 1000 rpm for 2 hours, then add remaining water, stir at 300-600 rpm for 45 minutes; The preparation method of the surface coating comprises: First, prepare bentonite solution and hydroxymethyl cellulose solution in the same way as the primer; Then, add component A of sj-8050 high-temperature binder and add component B while stirring at 300-500 rpm, continue stirring for 3 hours, then add bentonite liquid, hydroxymethyl cellulose liquid, surfactant, and defoaming agent in turn, stir evenly, add wear-resistant aggregate, first stir at a low speed of 40-60 rpm for 30 minutes, then stir at a high speed of 1000 rpm for 1 hour, add the remaining water, and stir at 300-600 rpm for 45 minutes.

[0080] Specifically, when preparing the topcoat and the basecoat, the method for preparing the bentonite liquid includes: adding 95 parts of water into a stirrer, adding 5 parts of sodium bentonite while stirring at 200-400 rpm, continuing to stir at a low speed for 30 minutes, and then stirring at a high speed at 800-1200 rpm for 60 minutes, and leaving it for 24 hours before use.

[0081] The method for preparing hydroxymethyl cellulose solution includes: adding 98 parts of water into a blender, adding 2 parts of hydroxymethyl cellulose while stirring at a low speed of 200-400 rpm, continuing to stir at a low speed for 30 minutes, stirring at a high speed of 800-1200 rpm for 60 minutes, and leaving it for 24 hours before use.

[0082] The preparation method of the water glass precursor includes: firstly adding water glass into a reaction kettle and heating it to 40-80°C, adding 0.2 parts of sodium tripolyphosphate while stirring at 300-500 rpm, stirring and dissolving, adding polyacrylamide, and stirring for 45 minutes.

[0083] According to the third aspect of the present invention, there is provided an application of the infrared energy-saving coating as described above in a water-cooled wall coating, wherein the water-cooled wall coating comprises a bottom layer and a surface layer, wherein the bottom layer is located between the water-cooled wall and the surface layer, wherein the thickness of the bottom layer is 50 to 150 μm, and the thickness of the surface layer is 40 to 100 μm.

[0084] In the present invention, when the base layer thickness is less than 50 μm, it may make it difficult for the silicon carbide particles to form a continuous heat conduction chain, causing the heat conduction network to break, leading to heat accumulation at the metal interface and causing local overheating. It may also reduce the coverage of the nanocatalyst layer, expanding the blind zone of the carbon deposit oxidation reaction, and may cause molten ash to penetrate the coating and accelerate corrosion. When the base layer thickness is greater than 150 μm, it may lead to increased thermal resistance, increased heat loss rate, delayed thermal response, and may also cause edge cracking due to thermal stress concentration.

[0085] When the surface thickness is less than 40μm, it may be difficult for brown corundum to form an effective stacking layer, resulting in wear-resistant protection failure, causing the risk of bottom exposure and accelerated erosion, and may also cause infrared radiation attenuation and cracking caused by thermal stress concentration.

[0086] When the surface thickness is greater than 100 μm, the effective infrared emissivity and heat absorption efficiency may be reduced due to the infrared radiation shielding effect, and the risk of thermal stress cracking may be increased, which may increase the probability of edge peeling.

[0087] Preferably, the total thickness of the surface layer and the bottom layer is 130-180 μm, wherein the bottom layer is 80-100 μm thick and the surface layer is 50-80 μm thick. At this thickness, the thermal conductivity, mechanical properties, and self-cleaning ability are all good. The bottom layer is preferably 90 μm thick, and the surface layer is preferably 60 μm thick.

[0088] In a preferred embodiment of the present invention, the method for treating the water wall coating comprises: First, the roughness of the water-cooled wall was treated by sandblasting to Rz = 40~80μm, and the viscosity of the base coating and the surface coating was adjusted to 1.35~1.45Pa·s; Then, spray the primer on the water-cooled wall and dry it at 20-30℃ for 24h. The thickness of the primer after drying is 20-150μm. Then, the topcoat is sprayed on the base layer and dried at 20-30°C for 24 hours. The thickness of the base layer after drying is 40-100 μm.

[0089] In this invention, the water-cooled wall is first roughened to an Rz of 40-80μm through sandblasting, effectively increasing the contact area between the coating and the water-cooled wall and improving adhesion. The viscosity of the base and top coatings is precisely controlled between 1.35 and 1.45 Pa·s to ensure uniform spraying and avoid defects such as sagging and dripping. The base and top coatings are sprayed in layers and dried at an appropriate temperature to achieve a dense, well-defined coating structure. The base layer thickness is controlled between 50 and 150μm, and the top layer thickness between 40 and 100μm. This fully utilizes the thermal conductivity and catalytic properties of the base coating and the wear resistance of the top coating, significantly improving the overall performance of the water-cooled wall coating, extending its service life, and reducing operating and maintenance costs.

[0090] Due to the good wettability between the surface coating and the base coating, when the surface coating is sprayed on the base coating, the surface coating can penetrate into the micropores of the base coating, which is beneficial to secondary sealing of the micropores of the base coating, thereby isolating the contact between the furnace gas and the water-cooled wall, and helping to avoid chemical corrosion of the water-cooled wall by chemical gases in the furnace gas.

[0091] The present invention first dries the bottom layer for 24 hours, so that the water glass is fully dehydrated to form a ≡Si-O-Si≡ network, and can also prevent subsequent surface solvent penetration from causing swelling of the bottom layer.

[0092] After the surface layer has dried for 24 hours, it can be sintered at high temperatures within the boiler to form a high-strength, hardness-like ceramic layer on the surface of the water-cooled wall tubes. The heating rate for natural sintering within the boiler is generally 5°C to 10°C / min, with furnace temperatures typically between 1300°C and 1600°C, flue gas temperatures between 800°C and 1200°C, and water-cooled wall surface temperatures between 300°C and 500°C.

[0093] After high-temperature sintering in the boiler, the alumina, zirconia, and other raw materials in the basecoat undergo a solid-phase reaction at high temperature, co-crystallizing with thermally conductive aggregates such as silicon carbide to form a stable ceramic phase skeleton. The brown corundum and zirconia in the topcoat further densify at high temperatures, interpenetrating with the cross-linked products of the SJ-8050 high-temperature binder to form a composite structure with ceramic properties. The two work synergistically to build a continuous, uniform, and dense ceramic-like layer on the surface of the water-cooled wall tubes.

[0094] In a preferred embodiment of the present invention, the coating treatment method further comprises the step of performing a curing treatment after the surface coating is dried; The curing process includes: first heating to 80°C at a rate of 2°C / min, keeping warm for 60 minutes, then heating to 150°C at a rate of 1.5°C / min, keeping warm for 30 minutes, then heating to 250°C at a rate of 3°C / min, keeping warm for 45 minutes, then cooling to 80°C at a rate of 1°C / min, and then cooling naturally.

[0095] In the present invention, the temperature is raised to 80°C at a rate of 2°C / min and held for 60 minutes to fully volatilize the residual solvent in the coating and reduce internal porosity. The temperature is then raised to 150°C at a rate of 1.5°C / min and held for 30 minutes. During this stage, the SJ-8050 high-temperature binder undergoes deep crosslinking, enhancing the interaction between the molecular chains. The temperature is then raised to 250°C at a rate of 3°C / min and held for 45 minutes to promote chemical bonding between various inorganic substances in the coating, making the ceramic-like layer structure more stable. Finally, the temperature is lowered to 80°C at a rate of 1°C / min and then cooled naturally. The slow cooling process avoids cracking of the coating due to thermal stress concentration and ensures the integrity of the coating. Through this series of curing treatments, the hardness, wear resistance, and thermal shock resistance of the coating are significantly improved, further extending the service life of the water-cooled wall, and helping to maintain good infrared radiation performance, continuously ensuring efficient heat exchange of the water-cooled wall, and improving energy saving effects.

[0096] In a preferred embodiment of the present invention, the bottom layer thermal expansion coefficient CTE = (9.2-9.8) × 10 -6 / K.

[0097] In the present invention, the thermal expansion coefficient of the bottom layer is (9.2~9.8)×10 -6 / K, it can effectively reduce the interfacial stress caused by the thermal expansion difference between the coating and the water-cooled wall during high-temperature operation, thus preventing the coating from falling off. At the same time, the thermal expansion coefficient of the bottom layer is slightly lower than that of the surface ceramic layer, which is about (10~12)×10 -6 / K, which creates a compressive stress state in the coating during the cooling process, improving its resistance to crack growth. This gradient thermal expansion design, combined with the dense structure formed during the curing process, significantly improves the coating's thermal shock resistance, allowing it to withstand the rapid temperature fluctuations during boiler startup and shutdown without cracking or flaking, significantly extending the coating's service life.

[0098] In a preferred embodiment of the present invention, the wetting angle of the surface layer is greater than 90°.

[0099] In the present invention, the surface layer is hydrophobic, and this hydrophobic surface layer can effectively reduce the contact area between the molten ash and corrosive gases in the high-temperature flue gas and the coating, thereby reducing the slagging rate and the degree of contamination. When fly ash particles hit the coating surface, the repulsive force generated by the high wetting angle makes it difficult for them to adhere or only forms loose accumulations, which are easily fallen off under the action of air flow or mechanical vibration, thus realizing the self-cleaning function. At the same time, the hydrophobicity can also prevent water vapor from condensing on the coating surface, reducing the risk of sulfuric acid dew point corrosion and stress corrosion cracking, and further protecting the water-cooled wall substrate material. Through this hydrophobic design, combined with the high thermal conductivity of the bottom layer and the high wear resistance of the surface layer, the coating system of the present invention comprehensively improves the anti-slagging, anti-corrosion and self-cleaning capabilities of the water-cooled wall, significantly reducing the maintenance cost and energy consumption during boiler operation.

[0100] Example The present application will be further described in detail below in conjunction with the embodiments. It will be understood that the specific embodiments described herein are only used to explain the relevant invention and are not intended to limit the invention. It should be noted that, unless there is a conflict, the embodiments and features in the embodiments of the present application may be combined with each other.

[0101] To better illustrate the present invention and facilitate understanding of the technical solutions of the present invention, typical but non-limiting embodiments of the present invention are as follows: The preparation methods of the primer and topcoat in each embodiment and comparative example include: 1. Preparation of base coating First, add water glass into the reactor and heat it to 40~80℃. Add 0.2 parts of sodium tripolyphosphate while stirring at 300~500 rpm. After stirring and dissolving, add polyacrylamide and stir for 45 minutes.

[0102] Add 95 parts of water into the blender, add 5 parts of sodium bentonite while stirring at 200-400 rpm, continue stirring at low speed for 30 minutes, then stir at high speed at 800-1200 rpm for 60 minutes, and leave it for 24 hours before use.

[0103] Add 98 parts of water into the blender, add 2 parts of hydroxymethyl cellulose while stirring at a low speed of 200-400 rpm, continue stirring at a low speed for 30 minutes, then stir at a high speed of 800-1200 rpm for 60 minutes, and leave it for 24 hours before use.

[0104] Then, add water glass precursor, bentonite liquid, hydroxymethyl cellulose liquid, surfactant and defoamer in sequence, stir at 300-600 rpm for 30 minutes, then add thermal conductive aggregate, stir at low speed of 40-60 rpm for 30 minutes, then stir at high speed of 1000 rpm for 2 hours, then add the remaining water, stir at 300-600 rpm for 45 minutes, and adjust the viscosity of the primer to 1.35-1.45 Pa·s.

[0105] 2. Preparation of surface coating First, add 95 parts of water into the blender, add 5 parts of sodium bentonite while stirring at 200-400 rpm, continue stirring at low speed for 30 minutes, then stir at high speed at 800-1200 rpm for 60 minutes, and leave it for 24 hours before use.

[0106] Add 98 parts of water into the blender, add 2 parts of hydroxymethyl cellulose while stirring at a low speed of 200-400 rpm, continue stirring at a low speed for 30 minutes, then stir at a high speed of 800-1200 rpm for 60 minutes, and leave it for 24 hours before use.

[0107] Then, add component A of the sj-8050 high-temperature binder and add component B while stirring at 300-500 rpm. Continue stirring for 3 hours, then add bentonite liquid, hydroxymethyl cellulose liquid, surfactant, and defoaming agent in sequence. After stirring evenly, add wear-resistant aggregate, first stir at a low speed of 40-60 rpm for 30 minutes, then stir at a high speed of 1000 rpm for 1 hour, add the remaining water, stir at 300-600 rpm for 45 minutes, and adjust the viscosity of the primer to 1.35-1.45 Pa·s.

[0108] The raw materials of each embodiment are as follows: Example 1 The primer includes the following raw materials in parts by weight: 20 parts of silicon carbide, 5 parts of cordierite, 5 parts of boron nitride, 6 parts of aluminum oxide, 6 parts of zirconium oxide, 5 parts of copper oxide, 25 parts of water glass, 0.2 parts of polyacrylamide, 0.2 parts of sodium tripolyphosphate, 0.2 parts of JFC surfactant, 0.15 parts of silicone defoamer, 1 part of bentonite, 0.1 parts of hydroxymethyl cellulose, 3 parts of Texanol ester alcohol, and 23.15 parts of water.

[0109] In the primer, the silicon carbide particle size (D50) is 8 μm, the copper oxide particle size is 200 nm, the catalyst and silicon carbide mass ratio is 1:4, and the cordierite and boron nitride mass ratio is 1:1.

[0110] The surface coating includes the following raw materials in parts by weight: 30 parts of silicon carbide, 6 parts of zirconium oxide, 5 parts of brown corundum, 30 parts of SJ-8050 high-temperature binder, 0.2 parts of JFC surfactant, 0.15 parts of silicone defoamer, 1 part of bentonite, 0.1 parts of hydroxymethyl cellulose, 3 parts of Texanol ester alcohol, and 24.55 parts of water.

[0111] In the surface coating, the particle size D50 of silicon carbide is 6 μm.

[0112] Then prepare the coating / steel substrate composite specimens: First, after cleaning the surface of the steel substrate, the sandblasting process is used to treat the roughness of the steel substrate to Rz=40~80μm, and the primer with a viscosity of 1.35~1.45Pa·s is placed in a spray can for spraying, and dried at 20~30℃ for 24h. After drying, the thickness of the bottom layer is 90μm. Then, the top layer paint with a viscosity of 1.35~1.45Pa·s is placed in a sprinkler and sprayed on the bottom layer. It is dried at 20~30℃ for 24h. After drying, the thickness of the bottom layer is 60μm.

[0113] Then, the combustion in the boiler was simulated and the solidification treatment was carried out. The heating rate was controlled at about 70℃ / min, the surface temperature of the steel substrate was controlled at about 400℃, and the sintering was carried out for 3.5h, followed by natural cooling.

[0114] Example 2 The difference from Example 1 is that in the primer, the particle size D50 of silicon carbide is 6 μm.

[0115] The rest is the same as in Example 1.

[0116] Example 3 The difference from Example 1 is that in the primer, the particle size D50 of silicon carbide is 10 μm.

[0117] The rest is the same as in Example 1.

[0118] Example 4 The difference from Example 1 is that in the surface coating, the silicon carbide particle size D50 is 8 μm.

[0119] The rest is the same as in Example 1.

[0120] Example 5 The difference from Example 1 is that in the primer, copper oxide is 6 parts, and the mass ratio of copper oxide to silicon carbide is 1:3.33.

[0121] The rest is the same as in Example 1.

[0122] Example 6 The difference from Example 1 is that in the primer, copper oxide is contained in an amount of 4.5 parts, and the mass ratio of copper oxide to silicon carbide is 1:4.44.

[0123] The rest is the same as in Example 1.

[0124] Example 7 Compared with Example 1, the difference is that the base coating contains 4 parts of boron nitride and 6 parts of cordierite, and the rest is the same as Example 1.

[0125] Example 8 Compared with Example 1, the difference is that the base coating contains 6 parts of boron carbide and 4 parts of cordierite, and the rest is the same as Example 1.

[0126] Example 9 Compared with Example 1, the difference is that the thickness of the bottom layer is 70 μm, the thickness of the surface layer is 40 μm, and the rest is the same as Example 1.

[0127] Example 10 Compared with Example 1, the difference is that the thickness of the bottom layer is 130 μm, the thickness of the surface layer is 90 μm, and the rest is the same as Example 1.

[0128] Example 11 Compared with Example 1, the difference is that the thickness of the bottom layer is 80 μm, the thickness of the surface layer is 50 μm, and the rest is the same as Example 1.

[0129] Example 12 Compared with Example 1, the difference is that the thickness of the bottom layer is 100 μm, the thickness of the surface layer is 80 μm, and the rest is the same as Example 1.

[0130] Example 13 Compared with Example 1, the difference is that in the process of preparing the coating / steel substrate composite sample, the curing treatment method is: first, the temperature is raised to 80°C at a rate of 2°C / min, and kept warm for 60 minutes, then the temperature is raised to 150°C at a rate of 1.5°C / min, and kept warm for 30 minutes, then the temperature is raised to 250°C at a rate of 3°C / min, and kept warm for 45 minutes, and then the temperature is lowered to 80°C at a rate of 1°C / min, and then naturally cooled.

[0131] Comparative Example 1 Compared with Example 1, the difference is that copper oxide is not used in the primer, and the rest is the same as Example 1.

[0132] Comparative Example 2 Compared with Example 1, the difference is that copper oxide is not used in the primer, but 5 parts of copper oxide are added to the surface layer. The rest is the same as Example 1.

[0133] Comparative Example 3 Compared with Example 1, the difference is that the thickness of the bottom layer is 40 μm, and the rest is the same as Example 1.

[0134] Comparative Example 4 Compared with Example 1, the difference is that the surface thickness is 30 μm, and the rest is the same as Example 1. The following tests were performed on Examples 1 to 13 and Comparative Examples 1 to 4: 1. Thermal expansion coefficient Thermal expansion testing was performed using a thermal dilatometer in accordance with GB / T 7320-2018, "Coefficient of Thermal Expansion of Coatings." The test specimens were sprayed with the primer, dried for 24 hours, and then cured according to the curing methods described in the Examples and Comparative Examples before measurement.

[0135] 2. Thermal conductivity The cured coating was tested according to GB / T 22588-2008 “Flash method for measuring thermal diffusivity or thermal conductivity”.

[0136] 3. Infrared emissivity According to GB / T 13488-2015 "Test method for infrared emissivity of materials", the cured coating is sampled and measured.

[0137] 4. Thermal shock performance test Heat to 500°C in a high-temperature muffle furnace, hold for 30 minutes, quench in cold water, and then heat again. Repeat the above cycle 45 times and observe the spalling rate.

[0138] 5. Adhesion After thermal shock cycles, the peeling condition was tested using the cross-hatch method with a spacing of 1 mm according to GB / T 9286.

[0139] 6. Coating hardness test With reference to standard GB / T 4340.1, a micro Vickers hardness tester was used with a load of 500g to perform surface hardness testing.

[0140] 7. High temperature corrosion resistance According to GB / T 25928-2010 "Test method for high-temperature corrosion resistance of metals and other inorganic coatings", the corrosion test was carried out in simulated flue gas (volume content: SO32%, HCl 1%, O2 15%, H2O 12%, nitrogen as the balance gas) at a temperature of 500℃±5℃ for 200h. The corrosion rate was calculated by weighing.

[0141] 8. Catalytic activity First, a carbon mixture gas (volume content of CO 10%, CH4 5%, O2 3%, N2 82%) was introduced and operated at 700℃ for 20 h; then it was switched to a CO / O2 mixture gas (CO 5%, O2 2.5%, N2 92.5%), maintained at 500℃, and the CO conversion rate was monitored by GC.

[0142] 9. Wetting angle The wetting angle was measured using a contact angle meter.

[0143] The test results are shown in Table 1.

[0144] Table 1 Test results of Examples 1 to 13 and Comparative Examples 1 to 4

[0145] The coating of Example 1 was applied to the water-cooled wall of a 600MW boiler in a power plant and operated continuously for 12 months. The coking rate was reduced by 68%, thermal efficiency was improved, exhaust temperature dropped by 18°C, coal consumption was reduced by 1.8g / kWh, maintenance costs were reduced, and soot blowing frequency was reduced from 2 times / day to 1 time / week.

[0146] The applicant states that while the above-described embodiments illustrate the process of the present invention, the present invention is not limited to the above-described process steps, nor does it imply that the present invention must rely on the above-described process steps for implementation. Those skilled in the art will appreciate that any improvements to the present invention, equivalent substitutions for the raw materials used, additions of auxiliary components, and selection of specific methods, etc., fall within the scope of protection and disclosure of the present invention.

Claims

1. A water-cooled wall self-cleaning infrared energy-saving coating, characterized in that: The coating comprises a base coating and a surface coating; The primer comprises the following raw materials in parts by weight: Thermally conductive aggregate, comprising 18-22 parts of silicon carbide, 4-6 parts of cordierite, 4-6 parts of boron nitride, 5-7 parts of aluminum oxide, and 5-7 parts of zirconium oxide; 4-6 parts of catalyst, including copper oxide and / or iron oxide; The first binder comprises 20-30 parts of water glass, 0.1-1 parts of polyacrylamide and 0.1-1 parts of sodium tripolyphosphate; 0.1-0.5 parts of the first surfactant; First defoamer, 0.1~0.3 parts; The first auxiliary agent includes 0.5-2 parts of bentonite, 0.05-0.2 parts of hydroxymethyl cellulose and 2-4 parts of Texanol ester alcohol; 5-30 parts water; The surface coating comprises the following raw materials in parts by weight: Wear-resistant aggregate, including 25-35 parts of silicon carbide, 5-7 parts of zirconium oxide and 4-6 parts of brown corundum; The second adhesive includes 25 to 35 parts of sj-8050 high temperature adhesive; 0.1-0.5 parts of the second surfactant; Second defoaming agent, 0.1~0.3 parts; The second auxiliary agent includes 0.5-2 parts of bentonite, 0.05-0.2 parts of hydroxymethyl cellulose and 2-4 parts of Texanol ester alcohol; 5~30 parts water 2. The infrared energy-saving paint according to claim 1, characterized in that: The particle size of silicon carbide in the primer is D50=7-9 μm, the particle size of the catalyst is 150-250 nm, and the particle size of silicon carbide in the surface coating is D50=5-7 μm.

3. The infrared energy-saving paint according to claim 1, characterized in that: The mass ratio of the catalyst to silicon carbide in the primer is 1:3.5-4.

5.

4. The infrared energy-saving paint according to any one of claims 1 to 3, characterized in that: The mass ratio of cordierite to boron nitride in the primer is 1:(0.9-1.1).

5. The method for preparing the infrared energy-saving coating according to any one of claims 1 to 4, characterized in that: The preparation method of the primer comprises: First, water glass precursor is prepared using water glass, sodium tripolyphosphate and polyacrylamide; bentonite solution with a concentration of 5% is prepared using bentonite and water; and hydroxymethyl cellulose solution with a concentration of 2% is prepared using hydroxymethyl cellulose and water; Then, add water glass precursor, bentonite solution, hydroxymethyl cellulose solution, surfactant and defoamer in sequence, stir at 300-600 rpm for 30 minutes, then add thermal conductive aggregate, stir at low speed of 40-60 rpm for 30 minutes, then stir at high speed of 1000 rpm for 2 hours, then add remaining water, stir at 300-600 rpm for 45 minutes; The preparation method of the surface coating comprises: First, prepare bentonite solution and hydroxymethyl cellulose solution in the same way as the primer; Then, add component A of sj-8050 high-temperature binder and add component B while stirring at 300-500 rpm, continue stirring for 3 hours, then add bentonite liquid, hydroxymethyl cellulose liquid, surfactant, and defoaming agent in turn, stir evenly, add wear-resistant aggregate, first stir at a low speed of 40-60 rpm for 30 minutes, then stir at a high speed of 1000 rpm for 1 hour, add the remaining water, and stir at 300-600 rpm for 45 minutes.

6. The use of the infrared energy-saving coating according to any one of claims 1 to 4 in a water-cooled wall coating, characterized in that: The water-cooled wall coating comprises a bottom layer and a surface layer, wherein the bottom layer is located between the water-cooled wall and the surface layer, the bottom layer has a thickness of 50-150 μm, and the surface layer has a thickness of 40-100 μm.

7. The use of the infrared energy-saving paint according to claim 6 in a water-cooled wall coating, wherein the treatment method of the water-cooled wall coating comprises: First, the roughness of the water-cooled wall was treated by sandblasting to Rz = 40~80μm, and the viscosity of the base coating and the surface coating was adjusted to 1.35~1.45Pa·s; Then, spray the primer on the water-cooled wall and dry it at 20-30℃ for 24h. The thickness of the primer after drying is 20-150μm. Then, the topcoat is sprayed on the base layer and dried at 20-30°C for 24 hours. The thickness of the base layer after drying is 40-100 μm.

8. The use of the infrared energy-saving coating in water-cooled wall coating according to claim 7, characterized in that: The coating treatment method further comprises the step of performing a curing treatment after the surface coating is dried; The curing process includes: first heating to 80°C at a rate of 2°C / min, keeping warm for 60 minutes, then heating to 150°C at a rate of 1.5°C / min, keeping warm for 30 minutes, then heating to 250°C at a rate of 3°C / min, keeping warm for 45 minutes, then cooling to 80°C at a rate of 1°C / min, and then cooling naturally.

9. The use of the infrared energy-saving paint in water-cooled wall coating according to claim 6, characterized in that: Bottom layer thermal expansion coefficient CTE = (9.2~9.8) × 10 -6 / K.

10. Use of the infrared energy-saving coating according to any one of claims 6 to 9 in a water-cooled wall coating, characterized in that: The wetting angle of the surface layer is greater than 90°.

Citation Information

Patent Citations

  • Ink composition and surface selective metallization method

    CN106634214A

  • Coating for reducing fly ash adhesion and preparation method and application thereof

    CN113249010A

  • Full color range reflective heat insulating coating system for construction and preparation method thereof

    WO2017028470A1

  • Water-based paint for glass steel tube, preparation method therefor, application method therefor and use thereof

    WO2020232719A1